Needs of older adults living in long-term care institutions: an observational study using Camberwell Assessment of Need for the Elderly - Tobis S (Dove Medical Press, 2018)
Sławomir Tobis,1 Katarzyna Wieczorowska-Tobis,2 Dorota Talarska,3 Mariola Pawlaczyk,1 Aleksandra Suwalska4 1Department of Geriatric Medicine and Gerontology, Poznan University of Medical Sciences, Poznan, Poland; 2Laboratory of Geriatrics, Department of Palliative Care, Poznan University of Medical Sciences, Poznan, Poland; 3Department of Preventive Medicine, Poznan University of Medical Sciences, Poznan, Poland; 4Laboratory of Neuropsychobiology, Department of Psychiatry, Poznan University of Medical Sciences, Poznan, Poland Introduction: No comprehensive needs assessment is performed routinely in Poland. Purpose: The goal of the study was to investigate the patterns of needs in older individuals living in long-term care institutions (LTCIs) using the Camberwell Assessment of Need for the Elderly (CANE) questionnaire, based on a previously published study protocol.Participants and methods: The study included 306 LTCI residents (age: ≥75 years) with the a Mini-Mental State Examination (MMSE) score of at least 10 points. The dependence in basic activities of daily living was measured using the Barthel index (BI). A screening for depression was performed using the Geriatric Depression Scale (GDS) in subjects with an MMSE score of ≥15 points. Thereafter, CANE was used to analyze needs receiving adequate support (met needs) and those without appropriate interventions (unmet needs).Results: The mean age of studied individuals was 83.2±6.0 years. They had 10.4±3.2 met needs and 0.8±1.2 unmet needs. Unmet needs were reported most commonly in the following areas: company (15.9%), psychological distress (14.0%), intimate relationship (11.4%), eyesight/hearing/communication (11.4%), and daytime activities (11.0%). The OR of having a large number of met needs (ie, above the median) was almost eight times higher in residents with a BI score of 0–49 points versus those with ≥ 80 points. The group between (with 50–79 points) had this parameter almost four times higher. The OR of having a large number of unmet needs depended neither on BI nor on GDS and was more than four times higher in the group of 10–19 MMSE points (ie, with symptoms of moderate dementia) versus subjects with 24–30 MMSE points (ie, without symptoms of dementia).Conclusion: We defined the target group with high probability of unmet needs and the areas in which resources and efforts should be concentrated. We believe that the results can be used to optimize care in LTCIs. Keywords: met needs, unmet needs, determinants, aged 75 and older, long-term care, optimization, CANE